2020
DOI: 10.1177/2041669520910167
|View full text |Cite|
|
Sign up to set email alerts
|

Icon Familiarity Affects the Performance of Complex Cognitive Tasks

Abstract: The purpose of this study was to investigate whether and how users' familiarity with symbols affects the performance of complex cognitive tasks which place considerable demands on working memory resources. We combined a modified math task paradigm with our previous icon familiarity training paradigm. Participants were required to complete a mathematical task involving icons to test their ability to perform complex cognitive tasks. The complexity of the task was manipulated using three independent variables: ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…No true assessment could be made about improvement in use of the Trauma App over time, as each participant only used it for 20–25 min. Previous studies of digital system use suggests that development of familiarity with the icons and images used in an application is required to improve operating efficiency [ 21 ]. This indicates that users may benefit from instruction on the TraumaApp but the addition of iconography would potentially increase the training demand.…”
Section: Discussionmentioning
confidence: 99%
“…No true assessment could be made about improvement in use of the Trauma App over time, as each participant only used it for 20–25 min. Previous studies of digital system use suggests that development of familiarity with the icons and images used in an application is required to improve operating efficiency [ 21 ]. This indicates that users may benefit from instruction on the TraumaApp but the addition of iconography would potentially increase the training demand.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity reflects the frequency with which icons are encountered [McDougall]. Icon usability studies validated that familiarity has been considered the usability of icons (Salman et al, 2012;Shen et al, 2020). It is evident that user performance improves dramatically as a result of learning.…”
Section: Discussionmentioning
confidence: 99%
“…No true assessment could be made about improvement in use of the Trauma App over time, as each participant only used it for 20-25 minutes. Previous studies of digital system use suggests that development of familiarity with the icons and images used in an application is required to improve 21 This indicates that users may benefit from instruction on the TraumaApp but the addition of iconography would potentially increase the training demand. Twenty of the 24 app users reported that they became more familiar with the app as they used it, although this is not supported by the data in Figure 4.…”
Section: Discussionmentioning
confidence: 99%